Publicness and strategic planning of public institutions: Evidence from Indonesia - Wisnu Untoro; Arifin Angriawan (Journal of Economics, Business, and Accountancy Ventura, 2016)
Strategic planning has become a very common practice in public organizations. Research shows the positive impacts of strategic planning on the firm performance. This study examines the impacts of publicness on planning formalization, flexibility and participation. Empirical evidence collected from Indonesia suggests that planning formalization associates negatively with publicness; and mediates the relationships between publicness, flexibility and participation. The results support the political control view of public organizations. The results suggest that public organizations need to be both formal and flexible. We also find the positive association between participation and flexibility.